Al-Majāz fī Khuṭbah Wāṣil ibn ʽAṭā’ al-Manzūʽah al-Rā’: Dirāsah Balāgiyah - Sitaresmi Dyaharah (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2021)
Wasil bin Atha 'was one of the pioneers of the Mu'tazilah (80-131 AD) writer who could not pronounce the letter Ra' well because of the plate/lisp. However, the drawback is that it can deliver beautiful and meaningful sermons. As for his famous sermon, he avoided the letter Ra '. Even without any preparation in his sermon he was able to deliver it well and clearly. Without the letter Ra 'in his sermon and without changing its meaning. In this study, the author uses one of the objects of the study of parrot science, namely looking at the beauty of majaz as an approach in discussing "al Majaz fii sermon Washil bin Atho' "al-Manzu'atu al-Ra"". One of the privileges of Washil bin Atho's sermon "al-Manzu'atu al-Ra'" has a balaghoh element, especially in the science of bayan, namely majaz, besides that it has a good uslub arrangement, and there are quotes from the verses of the Qur'an.